JEDDAH SEBAGAI MIQAT MAKĀNĪ: ANTARA ASPEK TA’ABBUDĪ DAN TA’AQQULĪ - Farizi, Mudrik (Investama : Jurnal Ekonomi dan Bisnis, 2021)
The universality of Islamic teachings has been hinted at by the Qur'an and al-hadith as the main source in estab- lishing Islamic laws. Many verses of the Qur'an and hadith texts which implicitly or explicitly state that Islam wants convenience for its people, not burdening something beyond their capabilities, and the large space of tolerance given when there are difficulties or dangers. threatening. One of the teachings in Islam that has received great atten- tion from Muslims is the pilgrimage. Hajj, in the pillars of Islam, is the fifth worship after the creed, prayer, fasting and zakat. This worship is carried out on certain days in the month of Dzulhijjah in the order of certain practices. Every hajj performer performs these practices in certain places as well. Among them is Mecca, where the pilgrims perform thawaf (around the Kaaba), sa'i (jogging), and tahallul (cut hair). Then, Arafah, a barren desert where pilgrims do contemplation and pray as much as possible. Then, Mina, where the pilgrims throw three kinds of jumrah, and so on until the Hajj ritual is complete. Along with the times, the implementation of the pilgri- mage also experienced various new phenomena that gave rise to new problems. Such as the problems regarding the timing of throwing jumrah on the days of Tashriq, the expansion of the area for the sa'i (mas'ā) and the place for throwing the jumrah (jamarāt), the expansion of the area for mabit in Mina, to the problem of determining the miqat then> nī. These new problems arose as a result of the times and the increasing number of pilgrims from time to time. The discussion in this paper is focused on the issue of whether or not King Abdul Aziz Airport Jeddah is to be used as a miqat makānī in initiating ihram inten- tions. However, the problem that arises later is about the limitations of the imple- mentation of the pilgrimage as carried out by the Prophet. This is because there have been changes in the situation and conditions that prevailed at the time of the Prophet, until now. The debate also took place around the understanding of the texts between the ta'abbudī aspect which left no room for ijtihad and the ta'aqqulī aspect which provided an opportunity for ijtihad to be carried out in it.